Analisis Faktor-faktor yang Berhubungan dengan Kejadian Hipertensi di Wilayah Kerja Puskesmas Tumbang Talaken Kabupaten Gunung Mas - Henny Dwi Hernita; Hermanto Hermanto; Kristin Rosela (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Hypertension is defined as an increase in systolic blood pressure >140 mmHg and diastolic blood pressure >90 mmHg, often triggered by unhealthy modern lifestyles. In the Working Area of Puskesmas Tumbang Talaken, Gunung Mas Regency, there was an increase in hypertension cases in 2021. Interviews with 10 patients revealed that 5 had a family history of hypertension and poor dietary habits, 3 were active smokers, and 2 rarely exercised and often felt tense due to work-related stress. The high number of hypertension cases warrants research into the factors associated with the incidence of hypertension in this area. The aim of this study is to analyze the factors related to hypertension incidence in Puskesmas Tumbang Talaken. Method: A correlational study with a cross-sectional approach. Data were collected using observation and questionnaires (physical activity, diet, Depression Anxiety Stress Scales, and smoking habits). The sample consisted of 180 respondents visiting Puskesmas Tumbang Talaken, selected using accidental sampling, and data were analyzed using the Chi-square correlation test. Results: The study showed significant relationships between genetic factors (p-value = 0.000), diet (p-value = 0.000), physical activity (p-value = 0.000), stress (p-value = 0.000), and smoking habits (p-value = 0.000) with the incidence of hypertension in the Working Area of Puskesmas Tumbang Talaken, Gunung Mas Regency. Conclusion: The focus of hypertension control programs should be integrated and include comprehensive services, such as promotive and preventive services through health promotion activities, as well as curative and rehabilitative services. Behavioral changes should focus on avoiding cigarette smoke, adopting a healthy diet, and engaging in regular physical activity.